2007
DOI: 10.1245/s10434-007-9502-9
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Transfusions in Patients Undergoing Surgery for Cancer

Abstract: Preoperative, operative, and postoperative factors may all contribute to high rates of anemia in patients undergoing surgery for cancer. Allogeneic blood transfusion is associated with both infectious risks and noninfectious risks such as human errors, hemolytic reactions, transfusion-related acute lung injury, transfusion-associated graft-versus-host disease, and transfusion-related immune modulation. Blood transfusion may also be associated with increased risk of cancer recurrence. Blood-conservation measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 114 publications
1
81
1
10
Order By: Relevance
“…Its effects on the immune system and recurrence have been described. 28 Saxena et al (2009) identified risk factors for requiring massive transfusion during CRS/HIPEC, which include preoperative anemia (hemoglobin <125 g/L), impaired coagulation profile (INR ≥1.2) and high tumour burden (PCI ≥16). 18 In an attempt to avoid this adverse event, our centre routinely performs intraoperative point-of-care (POC) coagulation testing and rotational thromboelastometry (ROTEM) in theatre every 2 h to aggressively detect and correct any abnormal results.…”
Section: Discussionmentioning
confidence: 99%
“…Its effects on the immune system and recurrence have been described. 28 Saxena et al (2009) identified risk factors for requiring massive transfusion during CRS/HIPEC, which include preoperative anemia (hemoglobin <125 g/L), impaired coagulation profile (INR ≥1.2) and high tumour burden (PCI ≥16). 18 In an attempt to avoid this adverse event, our centre routinely performs intraoperative point-of-care (POC) coagulation testing and rotational thromboelastometry (ROTEM) in theatre every 2 h to aggressively detect and correct any abnormal results.…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the widely studied immunosuppressive effects of allogeneic blood and the modulation of WBCs in allogenic vs. autologous transfusions [33]. A study investigating patients undergoing resection of gastric cancer randomized patients to allogeneic or autologous transfusion.…”
Section: Blood Transfusionmentioning
confidence: 99%
“…Five days after the operation, levels had returned to baseline for patients receiving autologous transfusions but remained suppressed in the allogeneic group [34]. Studies on this effect are controversial and remain inconclusive, as current literature does not clearly correlate TRIM with cancer recurrence [33,34].…”
Section: Blood Transfusionmentioning
confidence: 99%
“…[4] As allogeneic blood transfusion modulates the host immune system, it may also influence cancer recurrence. [77] As transfused leucocytes potentially alter circulating lymphocyte ratios and function, irradiated or leucocyte-depleted red-cells are frequently preferentially administered to oncology patients. However, even where leucocyte-depleted red cells are used, transfusion has been associated with decreased cancer-free survival and decreased overall survival in lung cancer [78] and a recent meta-analysis by Churchhouse and colleagues [79], while not reaching definitive conclusions, suggested an association between transfusion and decreased cancer-free survival.…”
Section: Interaction Between the Immune System And Cancer Cellsmentioning
confidence: 99%